(untitled) (Experimental biology, 2009)
Chemical composition is defined for studying reasons influencing on bad quality of antlers during its growth. The results of the research apparently showed that with growing of antlers content of ashes, calcium and phosphorus are increasing, amount of organic substances, which composition includes biologically active substances defining therapeutic characteristics, are decreasing.